Strategy to Build BUMDes Based on Digital Finance, Kuripan Village, Ciseeng District, Bogor Regency - Lusi Andriyani; Hasanah Hasanah; Izzatusolekha Izzatusolekha; Meisanti Meisanti; Oktaviana Purnamasari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Kuripan Village already has a Village Owned Enterprise (BUMDes), but it has not developed optimally. This is due to various factors, including the lack of understanding of the Village Apparatus regarding the importance of BUMDes and the unpreparedness of the village apparatus to manage and develop the BUMDes. Kuripan Village has abundant local resources such as agricultural land, plantations, livestock, fisheries, trade, and home industry. Commodities produced from Kuripan Village include tuber plants (cassava, etc.), cassava leaves, beef cattle, catfish, ornamental fish, rengginang, opaque and so on. UMJ community service implementation methodwith Funding Assistance for the Independent Study Policy Research Program, Independent Campus and Community Service Based on Private Higher Education Research Results in 2021, is by surveying and training on strategies to build BUMDes based on digital finance in Kuripan Village, Ciseeng District, Bogor Regency.The results obtained in community service,